Composites and MIL-STD-1530C. Issue 1 (11th March 2014) - Warren, Aaron; Heslehurst, Rikard; Wilson, Eric
Abstract : Purpose: – The purpose of this paper is to discuss changes to MIL-STD-1530C "Aircraft Structural Integrity Program" to account for the increased usage of composites in aircraft structures. Design/methodology/approach: – The evolution of the Aircraft Structural Integrity Program is presented and the five tasks that comprise the program are assessed for compatibility with composite aircraft structures. Findings: – This paper identifies a number of recommended changes to MIL-STD-1530C to ensure that the unique behaviour of composites is considered within the Aircraft Structural Integrity Program. Originality/value: – This paper recommends changes to MIL-STD-1530C to account for composite aircraft structures, thus providing assurance compatibility of the Aircraft Structural Integrity Program with composite materials.